Exploring influences of health and wellbeing in Sydney’s apartment living: A qualitative study of residents’ perceptions - Tamara Al-Obaidi; Jason Prior; Erica McIntyre (PLoS ONE, 2025)
In Australia, and internationally, a shift is occurring towards high-density apartment living with initiatives and research showing an increased interest in the relations between health, wellbeing and apartment buildings. This study explores the complex associations between residents’ perceptions of their health and wellbeing and the apartment buildings where they live within the context of Sydney, Australia, as the case study. It challenges the fragmented approach previously used to study healthy apartment living and their underlying assumptions that do not account for a coupled human-environment systems view of health and wellbeing concerning apartment living. Qualitative research was used, which included in-depth, semi-structured interviews with 17 residents living in different apartment buildings, supplemented by fieldwork and narrated photographs. Using a structured iterative thematic analysis process, 20 areas of health and wellbeing influence (themes) were identified and further categorised using synthetic thinking into diverse, context-dependent, multilevel, and pervading influences. The findings from this exploratory study suggest a complex view of health and wellbeing by residents of apartment buildings and provide novel and important insights that have not been previously reported in such breadth.